Telemedicine as an unexpected catalyst during and beyond the COVID-19 Pandemic - Kumar, Mahendra; Rani, Pushpa; Joshi, Binal; Soni, Roop Kishor; Kumari, Anita; Rohilla, Kusum K (Nepal Journal of Epidemiology, 2022)
Telemedicine that also known as the practice of medicine at a distance whereby information technology is used to ensure the delivery of medical care services. Telemedicine is not a new concept in the world and India.Indian Space Research Organization (ISRO) started telemedicine in India during year 2001 as a pilot project and in year 2005 Ministry of Health and family welfare started full time program of telemedicine by connecting all major health institutions. Telemedicine is connecting people across border and culture. The need-based changes are coming in telemedicine sectors such as smart apps, involvement of private sector players and high intensity internet connections reaching to rural areas and difficult demographic locations. During Covid-19 pandemic telemedicine benefited people by supplying health information and consultation without breaching them without breeching physical contact restrictions. The ease of access to telemedicine applications, its low cost, and the lack of infrastructure requirements propelled to become the top choice in these dayswhere physical distancingconsidered the aforementioned, thus we can conclude that telemedicine is promising tool.